(untitled) (Journal of Mechanical Engineering, 2015)
Energy ratio method (ERM), which is a widely used method for coupling loss factors (CLFs) measurement, may lead to numerical problems because of the inversion of a large dimension matrix. The improved energy ratio method proposed here simplified a series several-coupled system into a two-coupled system so that it becomes a two dimensions matrix instead of large dimensions one. Coupling loss factors of a series three-coupled structure are measured using this method. Vibrating responses of the structure has been tested and predicted with loss and coupling loss factors measured here in order to verify the accuracy of measured CLFs. The agreement of vibrating responses indicates the fact that the improved energy ratio method is of great accuracy and reliability.